CONDITIONS OF CREATING A HEALTHY ENVIRONMENT FOR MASTER'S STUDENTS IN THE PROCESS OF STUDYING A HEALTHY WAY FORMATION - Vorokhaev, O (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The purpose of the article is to analyze the conditions for creating a health preserving environment for the students of the magistracy in the course of studying the discipline «Healthy Lifestyle Formation». Research methodology is based on the combination of general (analysis, synthesis, generalization) and special (typological, systematic) methods with the principles of systematic and scientific. The scientific novelty of the work is that, using the methods of content analysis, the author analyzes the conditions of creating a health preserving environment for the students of the magistracy in the course of studying the discipline «Healthy Lifestyle Formation». The conditions for creating a health preservation environment for the students of the magistracy in the course of studying the discipline «Healthy Lifestyle Formation» are: increasing the students' knowledge in the basics of health, healthy lifestyles, physical education and sports; continuous improvement of teaching methodology (most students of the magistracy stated that they have a positive attitude and high interest in the lessons of the discipline «Healthy Lifestyle Formation» thanks to the teacher of this course); providing an emotional and competitive atmosphere. A prerequisite for the formation of interest in educational activities, in particular for the lessons in the discipline «Healthy Lifestyle Formation», is to give students of the magistracy the opportunity to show independence and initiative. Therefore, teachers of the discipline "Formation of a healthy lifestyle" are organizers of the educational process, which continuously interact with students and create conditions for their full physical, mental, spiritual, moral, social development and ensure the formation of conscious values of graduate students to their own health.